Forensic Dentistry - The Role of the Dentist in Human Identification - Vlasiadis, Konstantinos; Koutsamani, Maria (Clinical Medicine And Health Research Journal, 2023)
A dentist's role often involves screening, diagnosing, preventing, and treating a variety of oral diseases. However, it is equally important in both the medical and the judicial field through the identification of unidentified deceased individuals. For this reason, the science of Forensic Dentistry has been developed, the contribution of which is valuable, especially in cases of criminal acts or mass disasters, where the number of victims is high. Its work is characterized as demanding, in which case the immediate and effective action of specially trained and experienced professionals is necessary. The methods of identification used work with outline the collection, careful examination, radiographic and photographic imaging and recording of post-mortem evidence of teeth and their impressions on the skin alongside the jaws, the lips and the palatal rugae of mucosa in order to be compared with existing ante-mortem and to draw conclusions regarding the racial and age identification of the deceased as well as finding other useful information about him/her. The forensic dentist's contribution to the administration of justice is essential through keeping detailed records of patients and excellent cooperation with local authorities towards a valid and reliable identification process.